Analisis Pengaruh Kepemilikan Asing Good Corporate Governance Dan Sales Growth Terhadap Nilai Perusahaan - Rosiana Ismi; Titi Rapini; Riawan Riawan (The Academy Of Management and Business, 2022)
This study aims to see the effect of foreign ownership, good corporate governance and sales growth partially on firm value in various industrial companies listed on the Indonesia Stock Exchange (IDX). The period used is five years, starting from 2016-2020. Samples were taken using purposive sampling technique. The population in this study are various industrial companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The total population of 51 companies was obtained by 8 companies as samples with an observation period of five years (2016-2020). Based on the results of data analysis, it can be concluded that: 1) Foreign Ownership has an impact on Company Value, 2) Good Corporate Governance has an impact on Company Value, and 3) Sales Growth has no impact on Company Value.